Formulation of Acetaminophen Granules with Porang Tuber Amylum (Amorphophallusoncophyllus) that Meets the Parameters of Particle Size Distribution and Destruction Time - Arif Wijayanto; Juvita Herdianty (Universitas STRADA Indonesia, 2024)
Many farmers are interested in planting porang tubers, with many farmers planting porang tubers, the price of porang tubers will decrease during harvest . Porang tubers have several contents, namely starch, glucomannan, fiber, fat, protein, minerals and vitamins. Glucomannan content can be used as a tablet binder, thickener, gilling agent, film former, coating material emulsifier, and stabilizer. The purpose of this study was to determine the concentration of porang tuber flour as a binder in Acetaminophenum granules using the wet granulation method. Granules were made into three formulations with variations in the concentration of porang tuber flour, namely FI 5%, FII 7.5% and FIII 10%. GRANULES were tested for tablet uniformity, tablet hardness, tablet fragility , disintegration time, and granule size distribution. The data obtained were analyzed using Kruskal Wallis. The results of the analysis showed that variations in the concentration of porang tuber flour had different effects, based on the Kruskal Wallis analysis which showed a significant value of 0.10 (p> 0.05). The formulation that has a good physical quality test is formulation III, with a tablet hardness value of 6.84 kg and a disintegration time of 5.74 minutes which is almost close to the control (+) 14.27 kg and 6.38 minutes. The higher the concentration of porang tuber flour , the higher, the longer the disintegration time.